Introduction to security and network forensics - Buchanan, William J. , 1926-2005 (CRC Press, 2011)
Presents information in forensic computing and IT security. This volume offers practical insight to security and its importance in design, implementation, and the maintenance of systems. It provides guidance on creating systems that allow data to be gathered for future investigation of an event